A note on the relationship between television viewing and individual happiness - Mitesh Kataria; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In a recently published article, Bruni and Stanca (2008) suggest that television viewing has a negative impact on life satisfaction. In this note we argue that the empirical approach they use (an approach that omits the main effect of TV viewing in life satisfaction) is problematic. We estimate a microeconomic life satisfaction function and find mixed support for the claim that television viewing in general has a negative impact on individual happiness. Using a large cross- country comparison we find that there is a substantial heterogeneity across countries, which needs to be taken into account when concluding about television's effect on life satisfaction
Keywords: A12; D12; I31; 330; Relational goods; Subjective well-being; TV consumption; Happiness; Fernsehen; Lebenszufriedenheit; Soziale Beziehungen; Welt